(untitled) (Third Sector Social Economic Review, 2019)
The modern marketing approach focuses on demands and needs of consumers while taking into account the different characteristics of them. Determining the reasons that lead consumers to shopping, as well as determining which marketing efforts are more effective on consumers, are among the topics covered by the consumer literature. Hedonism generally means that in every aspect of life a person acts in a sense of pleasure. In order to understand how hedonic consumption has been shaped up to today, it is necessary to understand the concept of pleasure. The analysis of consumer behavior can play a limiting role in the scientific point of view of the relevant research topic by considering the consumption phenomenon in a single evaluation dimension. The analysis of the multi-faceted human element in both materialist and nutritious ways will help to make the determinations for consumer behavior healthier. This will also lead businesses and marketing managers to develop more efficient and effective strategies while improving their marketing efforts. The data obtained from 318 participants were examined by various statistical analysis methods and the relationship between hedonic consumption and materialism trends was determined. It was found that the scales used in the study had a sufficient level of reliability.